2020
DOI: 10.3389/fcell.2020.00363
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Colon Organoids From Inflammatory Bowel Disease Patients

Abstract: Inflammatory Bowel Diseases (IBD) are chronic inflammatory disorders, where epithelial defects drive, at least in part, some of the pathology. We reconstituted human intestinal epithelial organ, by using three-dimension culture of human colon organoids. Our aim was to characterize morphological and functional phenotypes of control (non-IBD) organoids, compared to inflamed organoids from IBD patients. The results generated describe the epithelial defects associated with IBD in primary organoid cultures, and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 38 publications
(43 reference statements)
5
77
0
Order By: Relevance
“…To generate human colonic organoids, fresh colonic tissues from control patients ( n = 13) were harvested and colon crypts were isolated and cultured in a three-dimensional Matrigel matrix for 10–12 days as previously described. 42 Organoids were generated in 48 wells in Matrigel plus culture medium (50% Wnt3a-conditioned medium (supernatant from L-Wnt3a cells), 50% advanced DMEM/F12, 100× GlutaMAX-CTS, 100× HEPES, serum-free B27, N2, N-acetylcysteine, nicotinamide, recombinant human epithelial growth factor, human Noggin, human R-spondin, gastrin, SB202190, LY2157299, and PGE2. The culture medium was changed every 2–3 days (without NAC and LY2157599).…”
Section: Methodsmentioning
confidence: 99%
“…To generate human colonic organoids, fresh colonic tissues from control patients ( n = 13) were harvested and colon crypts were isolated and cultured in a three-dimensional Matrigel matrix for 10–12 days as previously described. 42 Organoids were generated in 48 wells in Matrigel plus culture medium (50% Wnt3a-conditioned medium (supernatant from L-Wnt3a cells), 50% advanced DMEM/F12, 100× GlutaMAX-CTS, 100× HEPES, serum-free B27, N2, N-acetylcysteine, nicotinamide, recombinant human epithelial growth factor, human Noggin, human R-spondin, gastrin, SB202190, LY2157299, and PGE2. The culture medium was changed every 2–3 days (without NAC and LY2157599).…”
Section: Methodsmentioning
confidence: 99%
“…In our hands, we observed a rapid viability loss of organoids cultured in suspension (< 3 days) which restricts the use of this culture condition to short-term experimental treatments. Alternatively, incubation of human intestinal organoids with an inflammatory cocktail composed of tumor necrosis factor-alpha, interleukin-6 and interleukin-1 induced the inversion of organoid polarity [ 35 ]. This technique has not been applied yet to reverse epithelial polarity in farm animal organoids.…”
Section: Phenotype Of Livestock Intestinal Organoidsmentioning
confidence: 99%
“…Characterization of organoids derived from patients with IBD revealed a phenotype with decreased size and budding capacity, increased rate of cell death, luminal debris and partially inverted polarization of epithelial cells [106]. Global comparison of organoids from UC or CD patients and healthy controls showed that transcriptional and methylation differences seen in the intestinal epithelium were maintained in vitro [102,103,107].…”
Section: Modelling Epithelium-dependent Aspects Of Ibd With Organoidsmentioning
confidence: 97%
“…This was especially the case when organoids were generated from sites of severe inflammation [105]. A decrease in junctional proteins could also be induced in organoids from healthy donors by application of the proinflammatory cytokine TNF-α and/or IFN-γ [106,111]. However, the fixed pattern of changes of junctional proteins in organoids from patients with IBD was observed only on the protein level but not on the mRNA level [105].…”
Section: Modelling Epithelium-dependent Aspects Of Ibd With Organoidsmentioning
confidence: 99%